The Effect of Different Types of Quiet Eye Training on Kicking Skill in Children with High Motor Proficiency - Mehdi Yazdani; Mehdi Shahbazi; Jamal Fazel-Kalkhoran; Elaheh Arabameri (Vesnu Publications, 2019)
Introduction: The human uses vision to detect information about the task environment. Studies have shown that duration of quiet eye, motor performance, and efficiency in a number of tasks has improved using quiet eye training. The current study was to assess the effects of different types of quiet eye training on quiet eye and kicking skill in children with high motor proficiency. Materials and Methods: In this study, 45 boy students with high motor proficiency with age range of 7 to 10 years by performing a pretest phase, homogeneously divided in to three groups of baseline, and short-term and long-term quiet eye training. The study included pretest, acquisition, and posttest phases. In the pretest phase, the participants performed 4 soccer shots (Modified Christian Moore's Shot Test). The acquisition phase was done in 12 sessions, and 10 trials in per session. At the end of the last training session, the participants performed 4 soccer shots in the posttest phase. In each phase, visual information was recorded by the eye tracking system, and the accuracy of the soccer shot was recorded by the researcher. Data were analyzed using paired sample t-test and one-way ANOVA. Results: The different types of quiet eye training had a significant effect on accuracy of soccer shot (P = 0.001) and the duration of quiet eye (P = 0.001) of children with high motor proficiency. But there was no significant difference between each of the types of quiet eye training on the accuracy of soccer shot and the duration of quiet eye (P > 0.05 for both).